(untitled) (Journal of the College of Basic Education, 2022)
This study deals with the treatment of alternative perceptions of mathematical concepts through learning with a strategy based on constructive learning, which is the generative learning strategy in teaching mathematical concepts.The research aims to identify:1- Preparing an educational curriculum based on the use of the generative learning strategy that suits the capabilities of the research sample.2 - Learn about the impact of the educational program on learning and knowledge acquisition in football